2007
DOI: 10.1113/jphysiol.2007.145409
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+‐dependent generation of mitochondrial reactive oxygen species serves as a signal for poly(ADP‐ribose) polymerase‐1 activation during glutamate excitotoxicity

Abstract: Mitochondrial Ca2+ uptake and poly(ADP-ribose) polymerase-1 (PARP-1) activation are both required for glutamate-induced excitotoxic neuronal death. Since activation of the glutamate receptors can induce increased levels of reactive oxygen species (ROS), we investigated the relationship of mitochondrial Ca 2+ uptake and ROS generation, and the possibility that ROS increase is a required signal for PARP-1 activation in cultured striatal neurons. Based on the spatial profile of NMDA-induced ROS generation, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 72 publications
5
112
0
Order By: Relevance
“…This study suggested that Ca 2ϩ uptake and mitochondrial ROS production might be the early signaling events in the activation of PARP-1. 109 Recent studies 115 in an in vitro model of cardiomyocyte infection by T. cruzi support the previously described notion because we found that invasion by parasites triggered MPT and loss of membrane potential, which resulted in an inefficiency of the electron transport chain and increased ROS production. The ROS-induced DNA damage elicited PARP-1 activation; the latter, in turn, led to an increased formation of PARs.…”
Section: Parp-1-related Signaling Pathwayssupporting
confidence: 56%
See 1 more Smart Citation
“…This study suggested that Ca 2ϩ uptake and mitochondrial ROS production might be the early signaling events in the activation of PARP-1. 109 Recent studies 115 in an in vitro model of cardiomyocyte infection by T. cruzi support the previously described notion because we found that invasion by parasites triggered MPT and loss of membrane potential, which resulted in an inefficiency of the electron transport chain and increased ROS production. The ROS-induced DNA damage elicited PARP-1 activation; the latter, in turn, led to an increased formation of PARs.…”
Section: Parp-1-related Signaling Pathwayssupporting
confidence: 56%
“…47 The activation of PARP-1 under most of these conditions directly results from final DNA damage by oxidants or genotoxicity; yet, how the DNA damage signal is transmitted to PARP-1 remains under further investigation. Duan et al 109 recently elucidated a detailed pathway from an upstream stimulus to PARP-1 activation and mitochondrial release of AIF and cytochrome c in neurons. The researchers showed that glutamate excitotoxicity activates the N-methyl-D-aspartic acid receptor that leads to mitochondrial Ca 2ϩ overload and increased reactive oxygen species (ROS) production and PARP-1 activation.…”
Section: Parp-1-related Signaling Pathwaysmentioning
confidence: 99%
“…A classical view is that calcium-loaded mitochondria generate ROS, which trigger DCD and cell death [10,11]. However, it is not settled if oxidative stress precedes the DCD and is a causative factor or if it is a consequence of DCD [15,16]. Assuming that DCD is synonymous with calcium-induced mPT (which is controversial), our results favor the latter interpretation.…”
Section: Discussionmentioning
confidence: 44%
“…Excitotoxicity is a pathological feature of both acute and chronic neurodegenerative conditions [7][8][9]. Increased ROS production from mitochondria has been demonstrated following NMDA receptor stimulation in models of excitotoxicity and has also been coupled to mitochondrial loading of calcium [10][11][12][13][14][15]. However, the mechanism linking mitochondrial calcium loading and ROS production is currently unresolved [15][16][17], and studies in isolated brain mitochondria have yielded diverging results regarding the effect of calcium on mitochondrial ROS generation [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The function of NMDA receptor redox control or the connection to the mitochondria has yet to be established; however, we propose that ROS changes may be involved in a negative feedback system between mitochondria, a primary site for intracellular Ca 2+ storage/regulation, and NMDA receptor-mediated Ca 2+ entry. Mitochondrial ROS generation is increased by NMDA receptor activation unless blocked by the removal of extracellular Ca 2+ , mitochondrial uncouplers or Ca 2+ uniporter inhibitors (Duan et al, 2007;Dugan et al, 1995). A feedback loop between Ca 2+ influx and storage could be utilized to prevent excessive uptake leading to cell death.…”
Section: Research Articlementioning
confidence: 99%